A Exposição Universal 2020 e seu legado para São Paulo: construção e gestão do Centro de Convenções - Rossi, Carla (2013)
This research was developed in order to discuss the transversal management of public policies on human rights and social participation in São Paulo, taking in account the proposals and practices of the newly created Secretariat of Human Rights and Citizenship (SMDHC). From the case study method developed by Robert Yin (2001), this research sought to understand the structure of the Secretariat, the mechanisms by which it develops its role both as articulator and public policy makers in their field and the key challenges on the horizon of transversal management of public policies. Based on a theoretical framework on the concepts of transversality and intersectoriality and their relationship with the public policies on human rights and social participation six variables were established for analysis that guided this research – peopleand administrative management, information management, federalism, political and institutional capacity, strategic management and social participation. Resulting from the analysis, this research concludes that the radicalization of transversality as a management model enables the universalization of public policies on human rights in the city of São Paulo. Proposals were formulated to contribute to transversal management of public policy, under the perspective of defending and promoting human rights and social participation and thereby strengthen the coordinating role of the Secretariat throughout the City.